2009
DOI: 10.1080/17513750802660914
|View full text |Cite
|
Sign up to set email alerts
|

The influence of sexually active non-reproductive groups on persistent sexually transmitted diseases

Abstract: We describe several population models exposed to a mild life-long sexually transmitted disease, i.e. without significant increased mortality among infected individuals and providing no immunity/recovery. We then modify these models to include non-reproductive groups consisting of those isolated from sexual contact and those who are sexually active but infertile due to choice, medical or other reasons. We analyse the potential effect on the dynamics of the population. We are interested in how the isolated class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…We can, therefore, establish conditions on the parameters so that This result is similar to the one obtained in our previous paper (Maxin and Milner, 2007) involving SI-type one-sex models. In that case the transmission process involved only one parameter, l, the force of infection coefficient.…”
Section: Article In Presssupporting
confidence: 79%
See 3 more Smart Citations
“…We can, therefore, establish conditions on the parameters so that This result is similar to the one obtained in our previous paper (Maxin and Milner, 2007) involving SI-type one-sex models. In that case the transmission process involved only one parameter, l, the force of infection coefficient.…”
Section: Article In Presssupporting
confidence: 79%
“…We used the demographic model with isolation from reproduction to analyze the impact of abstaining from sexual activity on the evolution of a persistent sexually transmitted disease. This was a continuation of our previous work using one-sex S2I type models (Maxin and Milner, 2007). We found that, just as in the one-sex case, the isolation from sexual activity has both a demographic and an epidemiological impact in the sense that the isolated group can induce a stable disease free equilibrium in an otherwise endemic population.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Our next objective related to the present research is to investigate if similar results can be obtained using two-sex models. The influence of sexually abstaining groups on STD dynamics has been analyzed in [Maxin 2009;Maxin and Milner 2009] using a gender structured logistic model. We intend to extend that model to include vertical transmission.…”
Section: Discussionmentioning
confidence: 99%